(untitled) (Journal of the College of Basic Education, 2022)
Athletics is one of the most important individual games in the world, which is widely practiced and includes many activities, including short-distance running, long-distance running, and the marathon, as well as throwing events and jumping and jumping events, which require educational and training curricula in order to develop these events. In order to promote the good level of middle schools in the activities of athletics with all its activities and the various methods and methods of teaching and training in a way that suits the levels of the age groups that exist in these schools, the teacher must be well acquainted with all methods and methods of teaching. The importance of this research lies in the application of the cooperative method, one of the effective learning methods, by preparing an educational curriculum to teach the research sample of middle school students who are learning the skill for the first time. And the Distinguished High School for Boys, which is affiliated to the Directorate of Education of Rusafa First, was chosen in the intentional way, due to the presence of suitable arenas for practicing athletics, including javelin throwing. The number of its students is (33) students by lottery. The most important stage of learning javelin throwing is the approach run and the five steps, as well as javelin throwing and stability well. The curriculum has been prepared within the cooperative method, which means dividing the students into groups and assigning them to work Together, cooperating according to an organizational structure for teamwork, so that the members of each group cooperate and integrate among themselves in order to learn according to clear and specific roles with Emphasizing that each member of the group learns the required educational material, and that learning takes place in a comfortable atmosphere free of tension and anxiety, and this leads to the students’ motivation to rise significantly, allowing the student to adapt greatly to these influential stages, which leads to a significant improvement in performance, After completing the application of the educational curriculum, post-tests were conducted, and after processing the results of the tests by using the statistical package (SPSS), the conclusions showed the superiority of the experimental group over the control group in the post tests, as a result of the experimental group’s use of the cooperative learning method over the traditional (command) method used by the control group, and the recommendations came to the need to use the cooperative learning method in learning this skill or other skills in a way that ensures the advancement and improvement of performance at the level of students.